Metabolomic Diversity and Identification of Antibacterial Activities of Bacteria Isolated From Marine Sediments in Hawai’i and Puerto Rico - Kashfi, Ruhnaz; Kelsey, Charles; Gang, David Jorgen; Call, Douglas R.; Gang, David R. (Frontiers in Molecular Biosciences, 2020)
Antibiotic resistance is a growing concern worldwide and consequently metabolomic tools are being applied increasingly in efforts aimed at identifying new antimicrobial compounds. Marine bacteria-derived compounds have shown great promise in this area. A metabolomics-based study was undertaken to study the diversity of secondary metabolites from marine sediment bacteria isolated from different locations of Hawai’i and Puerto Rico. This effort included characterizing the biodiversity in the sediment samples and searching for antibacterial activity and associated compounds. Bacterial strains were isolated using several different nutrient agars and culture conditions. DNA sequencing (16s rDNA) was used for phylogenetic characterization. Antibacterial activity was assessed against antibiotic-resistant strains of Escherichia coli, Salmonella enterica, Acinetobacter baumannii, Staphylococcus aureus and Enterococcus faecalis. Ethyl acetate extracted bacterial secondary metabolites were measured by ultra-performance liquid chromatography-mass spectrometry, processed in Progenesis QI and further analyzed by partial least squares-discriminant analysis using MetaboAnalyst 3. Among the strains (n=143) that were isolated from these two geographical areas and tested for antibiotic activity, 19 exhibited antibacterial activity against at least one antibiotic-resistant human pathogen. One strain from Hawai’i possessed broad-spectrum activity against all five pathogens. Metabolite profiles were diverse and separated the strains into two clusters in PCA analysis that mirrored geographical origin of the isolated strains. A diversity of bacteria and potential antibacterial compounds were observed in this study. Marine environments represent an opportunity to discover a rich diversity of antibacterial compounds for which resistance mechanisms may be uncommon in human pathogens.